SCIENTIFIC - METHODOLOGICAL PROBLEMS OF PROJECT MANAGEMENT STRATEGY IN CONSTRUCTION (Marketing Journal, 2026)
The application of project management concepts in construction organizations prompts a reconsideration of the functional and strategic aspects of their management systems. In this case, clarity and validity of strategic objectives serve as the primary source of management effectiveness. This article analyzes the importance of the construction period in project management and its role in strategy selection, and presents the authorʼs methodological approach.
Keywords: project management; construction project; construction timeframe; strategic goal